Parametric studies on process parameters of selective laser melting - Loo, Andy Junxiang (2018)
Additive manufacturing (AM) is an important technology, which is making rapid advances in many industrial sectors in the past years. AM is also known as direct digital manufacturing, free-form fabrication, and three-dimensional (3D) printing. AM has environmental and ecological benefits alongside providing design freedom to manufacturing. AM can be categized into seven categories and three distinctive features powder bed, powder feed and wire feed systems. In this final year project, the focus will be on powder bed fusion process using selective laser melting (SLM). Selective laser melting is an AM technology which processes metallic materials in the form of powder. When an optimized set of parameters are used to print parts, parts that are close to full density can be achieved. PH 15-5 stainless steel was used in this study as the material for investigation. The objective of this study is to develop a set of optimized parameters using the selective laser melting process. The study will include research on the effects of different process parameters and the analysis of the mechanical experiment done. Design of experiment (DOE) and Analysis of variances (ANOVA) has been performed to determine the factors with significant effects. It was found that hatch spacing has the highest effects on the parts density. After optimization, the density obtained is above 99% and the ultimate tensile strength (UTS) is within the American society for testing and materials (ASTM) standards. A further recommendation to improve this study is included in the conclusion.